MINERALOGICAL AND CHEMICAL TRANSFORMATION OF OLDOINYO LENGAI NATROCARBONATITES, TANZANIA - Zaitsev A.N.; Keller J. (My University, 2006)
The minerals of Oldoinyo Lengai natrocarbonatite lavas are unstable under atmospheric conditions. Subsolidus mineral assemblages in natrocarbonatites were studied in 105 samples from contemporary eruptions ranging from present day to about 100 years old. The subsolidus minerals in natrocarbonatites were formed (i) along cracks on the lava surface from hot gases escaping during cooling, (ii) as atmospheric alteration by solution of water-soluble minerals, in particular halides and gregoryite, and by hydration of nyerereite under the influence of meteoric water and (iii) by reaction with fumarole gases. After solidification, the lavas were cut by a network of thin cracks, the edges of which are covered by polymineralic encrustations. Samples collected 2-24 h after eruption contain nahcolite, trona, sylvite, and halite with accessory kalicinite and villiaumite. Atmospheric humidity results immediately (≥ 2 h after eruption) in alteration of black lavas that is marked by the appearance of white powdery thermonatrite with nahcolite on the lava surface. Subsequent reaction (weeks, months, years) of natrocarbonatite with meteoric water and the atmosphere results in the formation of pirssonite, gaylussite, shortite, trona, thermonatrite, nahcolite and calcite. Generally, the first important step is the formation of pirssonite and the end-members are calcite carbonate rocks or loose aggregates. Fumarolic activity is common for the active northern crater of the volcano. Reaction of hot (54-141 °C) fumarolic gases with natrocarbonatite leads to the formation of sulphur, gypsum, calcite, anhydrite, monohydrocalcite, barite and celestine. Changes in mineralogy of the natrocarbonatite lead to substantial chemical transformation. The most obvious chemical changes in this process are the loss of Na, K, Cl and S, combined with an increase in H2O, Ca, Sr, Ba, F and Mn. The oxygen and carbon isotopic composition of altered natrocarbonatites shows a significant shift from the primary "Lengai Box" to high values of δ18O and δ13C. Calcite exhibits δ13C values between - 2‰ and - 4‰ PDB and δ18O values of + 23‰ to + 26‰ SMOW. The observed assemblages of secondary minerals formed by reaction with atmosphere and meteoric water, the changes in chemical composition of the natrocarbonatite and field observations suggest that alteration of natrocarbonatite is an open-system low-temperature process. It takes place at temperatures between 8 and 43 °C with the addition of H2O to the system and the removal of Na, K, Cl and S from the carbonatites. Low-temperature thermodynamic models developed for alkali carbonate systems can be used for the interpretation of Oldoinyo Lengai subsolidus mineralization. © 2006 Elsevier B.V. All rights reserved.
Keywords: ALTERATION; NAHCOLITE; NATROCARBONATITE; OLDOINYO LENGAI; PIRSSONITE; SHORTITE CALCITE; THERMODYNAMIC MODEL